1997
DOI: 10.1159/000227690
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Radiotherapy – 5 Years of Experience in the Palliative Treatment of Recurrent and Advanced Head and Neck Cancers

Abstract: Recurrent and advanced cancer in the head and neck region is usually associated with limited therapeutic concepts and a dismal prognosis. Efforts mainly focus on palliative treatment in order to improve the patient’s quality of life. From May 1989 to December 1994, a total of 120 intra-operative radiotherapy (IORT) procedures with high-energy electron beams (mean energy: 7 MeV; mean dose: 20 Gy) were performed in 95 patients. Therapy was usually performed under endotracheal anaesthesia (84%). There were 91 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Concurrently, Spaeth et al [ 33 ] evaluated the palliative efficacy of IORT treatment from May 1989 to December 1994, in a total of 120 sites in 95 patients predominantly suffering from recurrence in lymph nodes (75.8%) and primary site (11.7%). To a lesser extent, IORT constituted part of the initial treatment (12.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, Spaeth et al [ 33 ] evaluated the palliative efficacy of IORT treatment from May 1989 to December 1994, in a total of 120 sites in 95 patients predominantly suffering from recurrence in lymph nodes (75.8%) and primary site (11.7%). To a lesser extent, IORT constituted part of the initial treatment (12.5%).…”
Section: Resultsmentioning
confidence: 99%
“…However, long-term survival rates do not seem to conform in all series. [ 26 , 31 , 33 , 34 , 36 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…This visualization allows treatment with radiation even after prior delivery of full courses of radiation therapy. Although we did not analyze the incidence of treatment‐related complications in the present series, others have demonstrated that IORT is well tolerated for the treatment of head and neck cancers and does not increase perioperative morbidity or mortality 29–31…”
Section: Discussionmentioning
confidence: 92%
“…Locoregional control using IORT for recurrent head and neck cancer has been reported by a number of groups 4,6–8 . Adequate palliation and local control is not generally achieved with IORT when gross residual disease remains in situ, although some short‐term benefit may exist 9 . IORT has the greatest benefit for patients in whom clear or close microscopic margins are surgically obtained 6 .…”
Section: Discussionmentioning
confidence: 99%
“…4,6 -8 Adequate palliation and local control is not generally achieved with IORT when gross residual disease remains in situ, although some short-term benefit may exist. 9 IORT has the greatest benefit for patients in whom clear or close microscopic margins are surgically obtained. 6 Assessing IORT-related morbidity is challenging when considering the heterogeneity of the patients treated and the aggressive prior therapy many have already received.…”
Section: Intraoperative Radiation Therapymentioning
confidence: 99%